Advanced Dairy Chemistry Volume 3: Lactose, Water, Salts and Minor Constituents - McSweeney, Paul L. H.; Fox, Patrick F. (Springer New York : Imprint: Springer, 2009)
The Advanced Dairy Chemistry series was first published in four volumes in the 1980s (under the title Developments in Dairy Chemistry) and revised in three volumes in the 1990s. The series is the leading reference source on dairy chemistry, providing in-depth coverage of milk proteins, lipids, lactose, water and minor constituents. Advanced Dairy Chemistry Volume 3: Lactose, Water, Salts, and Minor Constituents, Third Edition, reviews the extensive literature on lactose and its significance in milk products. This volume also reviews the literature on milk salts, vitamins, milk flavors and off-flavors and the behaviour of water in dairy products. Most topics covered in the second edition are retained in the current edition, which has been updated and expanded considerably. New chapters cover chemically and enzymatically prepared derivatives of lactose and oligosaccharides indigenous to milk. P.L.H. McSweeney Ph.D. is Associate Professor of Food Chemistry and P.F. Fox Ph.D., D.Sc. is Professor Emeritus of Food Chemistry at University College, Cork, Ireland.